Evaluation of a new vaccine against Staphylococcus aureus mastitis in dairy herds of southern Chile. I. Challenge trial - Mella, Armin; Ulloa, Fernando; Valdés, Iván; Olivares, Nicolás; Ceballos, Alejandro; Kruze, Juan (Austral Journal of Veterinary Sciences, 2017)
S. aureus is the most frequently isolated mastitis pathogen in southern Chile. Hygiene during milking time and DCT have not been successful to control this pathogen. Vaccination has been suggested as a useful tool to combat mastitis and several vaccines have been developed and evaluated worldwide. This study presents the results of a pilot trial to evaluate the effects of a new vaccine produced in Chile against S. aureus mastitis on udder health, humoral immune response, and milk production after an experimental intramammary challenge with a heterologous S. aureus strain. Four 2 mL doses of the vaccine were administered intramuscularly to five pregnant heifers free of IMI infections, using another five heifers as controls. Ten days after last immunisation two mammary quarters of all heifers were challenged with a pathogenic strain of S. aureus. Heifers were monitored for clinical signs, bacterial count, SCC, differential leukocyte count in blood, S. aureus antibody, and milk yield during 14 days after challenge. No systemic effects were observed in any of the challenged heifers, and severe clinical cases were only observed in the control group. The SCCs were always higher in heifers of the control group. The challenged quarters of the control group yielded the highest counts of S. aureus, but no significant difference was observed between vaccinated and non-vaccinated groups. Serum antibody titres were twice as high in the vaccinated group compared to the control group, and average milk yield reduction was lower in the vaccinated group. In conclusion, this vaccine was able to stimulate the humoral immune response of vaccinated heifers which could have a beneficial effect against new IMI by S. aureus and help to combat this mastitis pathogen.